CALIBRATION OF RICHARDS' AND CONVECTION-DISPERSION EQUATIONS TO FIELD-SCALE WATER FLOW AND SOLUTE TRANSPORT UNDER RAINFALL CONDITIONS - Jacques D.; Simunek J.; Timmerman A.; Feyen J. (My University, 2002)
In this paper, the applicability of Richards' equation for water flow and the convection-dispersion equation for solute transport is evaluated to model field-scale flow and transport under natural boundary conditions by using detailed experimental data and inverse optimization. The data consisted of depth-averaged time series of water content, pressure head and resident solute concentration data measured several times a day during 384d. In a first approach, effective parameters are estimated using the time series for one depth and assuming a homogeneous soil profile. In a second approach, all time series were used simultaneously to estimate the parameters of a multi-layered soil profile. Water flow was described by the Richards' equation and solute transport either by the equilibrium convection-dispersion (CDE) or the physical non-equilibrium convection-dispersion (MIM) equation. To represent the dynamics of the water content and pressure head data, the multi-layered soil profile approach gave better results. Fitted soil hydraulic parameters were comparable with parameters obtained with other methods on the same soil. At larger depths, both the CDE- and MIM-models gave acceptable descriptions of the observed breakthrough data, although the MIM performed somewhat better in the tailing part. Both models underestimated significantly the fast breakthrough. To describe the breakthrough curves at the first depth, only the MIM with a mixing layer close to the soil surface gave acceptable results. Starting from an initial value problem with solutes homogeneously distributed over the mobile and immobile water phase was preferable compared to the incorporation of a small layer with only mobile water near the soil surface.
Keywords: PARAMETER OPTIMIZATION; NUMERICAL MODELING; UNSATURATED ZONE; WATER AND SOLUTE TRANSPORT